The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1001/jamasurg.2017.6159
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Delayed Intracranial Hemorrhage in Older Patients After Blunt Head Trauma

Abstract: Overall, the incidence of delayed intracranial hemorrhage in older adults who have blunt head trauma is low, including patients taking an anticoagulant or antiplatelet medication. These findings suggest that routine observation and serial cranial computed tomography may not be necessary in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
48
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 18 publications
6
48
0
Order By: Relevance
“…Our result of the highest ICH figure being in VKA patients agrees with many studies in the literature [ 9 , 10 , 17 , 33 , 40 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our result of the highest ICH figure being in VKA patients agrees with many studies in the literature [ 9 , 10 , 17 , 33 , 40 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ].…”
Section: Discussionsupporting
confidence: 93%
“…Minor head injury is defined as a patient with a history of loss of consciousness, amnesia, or disorientation and a Glasgow Coma Scale (GCS) score of 13–15 [ 1 , 2 ]. Anticoagulant medications are commonly used for a variety of indications [ 3 , 4 , 5 , 6 , 7 , 8 , 9 ], and it is widely believed that preinjury use of these medications increases the risk of traumatic intracranial injury and worsens clinical outcomes after blunt head trauma [ 10 , 11 , 12 , 13 ]. This belief is based largely on biological plausibility and retrospective cohort studies [ 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results of our study, with only one clinically significant case of delayed intracranial hemorrhage (0.3% in the repeat CT group, 0.1% in total), support other investigations which concluded that a routine repeat CT is not necessary for patients with antithrombotic therapy, due to the low clinical significance of most detected DIH [27,28,29,30,31,32]. The single case of a clinically significant DIH in our study showed an altered neurological status and would therefore have received an additional CT during the observation period regardless of clinical protocol for routine repeat CT.…”
Section: Discussionsupporting
confidence: 88%
“…Despite all guidelines, it is still necessary to make decisions based on risk stratification while considering the consequences for the individual patient. Chenoweth et al [28] found a 0.3% rate of DIH in their prospective study including patients with and without ATT, and concluded that “this (the low risk of DIH and fact that they can occur later than 24 h) highlights the importance of clinical judgment regarding the severity of trauma, additional injuries, and ability to monitor the patient for deterioration when making decisions about admission for older patients after blunt head trauma.”…”
Section: Discussionmentioning
confidence: 99%
“…5 The reported risk of delayed ICH after head injury has varied in the literature from 0% to 4%. [10][11][12][13][14][15][16] Several clinical guidelines highlight the risk of traumatic delayed ICH in patients taking antiplatelet agents. [17][18][19] According to the 2014 National Institute of Health and Care Excellence guidelines on head injury, for patients on aspirin or clopidogrel, 'the reference standard should include CT head scan and a follow-up period of sufficient duration to capture delayed bleeding, for example, at 7 days and 1 month'.…”
Section: Introductionmentioning
confidence: 99%